Constraints on the major sources of dissolved organic carbon in Alpine ice cores from radiocarbon analysis over the bomb‐peak period. Issue 8 (16th April 2013) - May, B.; Wagenbach, D.; Hoffmann, H.; Legrand, M.; Preunkert, S.; Steier, P.
Abstract : [1] Radiocarbon ( 14 C) has proven to be a powerful tool in distinguishing modern and fossil fuel sources contributing to organic aerosols. By applying this concept to ice core records of the dissolved organic carbon (DOC) fraction, we developed a setup dedicated to the extraction of DOC from Alpine ice core samples for 14 C microanalysis. With respect to the difficulties and limitations of this analytical method, it is shown that a total process blank mass of (6 ± 3) μgC with a 14 C signature of (0.71 ± 0.17) can be obtained, corresponding to a minimum sample size between 200 g for industrial and 800 g for pre‐industrial ice. Radiocarbon analyses of eight DOC ice core samples from the high accumulation glacier Col du Dôme (European Alps) were mainly performed over the bomb‐peak period. These data, being associated with snow deposition over the summer half‐years, show an overall mean fossil contribution of (25 ± 9) %. Adaptation of the DO 14 C values to the atmospheric 14 CO2 record revealed that the biogenic input to ice core DOC is associated with a fast recycling biospheric component, likely linked to a turnover time of less than 3 years. Key Points: First time 14C measurements on Dissolved Organic Carbon from Alpine ice cores Companion to DOI:10.1002/jgrd.50201 Companion to DOI:10.1002/jgrd.50202